Truth and psychoanalysis (2014)
In the section dedicated to theanalysis of the passage of the Bibleabout Pilate’s judgment of Jesus(volume II of the book Jesus ofNazareth), Joseph Ratzinger, betterknown as Pope Benedict XVI,emphasizes the serious implicationsfor human existence of insisting ona pragmatic answer to the question“What is truth?”, formulated at thetime by the Roman procurator. Inanother context, the ColombianCommission of Jurists also raisesthe question of the definition oftruth in its book Verdad, justiciay reparación. Algunas preguntas yrespuestas (2006) [Truth, Justice,and Reparation. Questions andAnswers]. These totally differentsources are used in the article tocontrast Ratzinger’s argument withthe psychoanalytical perspectiveon truth introduced by Lacan inSeminar 17, The Reverse Side ofPsychoanalysis.